1994
DOI: 10.1148/radiology.193.3.7526414
|View full text |Cite
|
Sign up to set email alerts
|

Covered, expandable esophageal metallic stent tubes: experiences in 119 patients.

Abstract: Treatment with placement of a covered expandable stent tube is effective in most patients with dysphagia due to malignant esophogastric strictures and is less effective in patients with benign strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
122
0
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(127 citation statements)
references
References 0 publications
1
122
0
4
Order By: Relevance
“…Aspiration remains a problem even after successful stent placement because of abnormal penistalsis of the esophageal wall due to tumor infiltration and stent placement [24]. Furthermore, 5-1 5% of patients with esophageal cancer will develop esophagotracheal fistulas with subsequent risk of aspiration [3,20,24].…”
Section: Twentymentioning
confidence: 99%
See 1 more Smart Citation
“…Aspiration remains a problem even after successful stent placement because of abnormal penistalsis of the esophageal wall due to tumor infiltration and stent placement [24]. Furthermore, 5-1 5% of patients with esophageal cancer will develop esophagotracheal fistulas with subsequent risk of aspiration [3,20,24].…”
Section: Twentymentioning
confidence: 99%
“…Aspiration remains a problem even after successful stent placement because of abnormal penistalsis of the esophageal wall due to tumor infiltration and stent placement [24]. Furthermore, 5-1 5% of patients with esophageal cancer will develop esophagotracheal fistulas with subsequent risk of aspiration [3,20,24]. We had no cases of aspiration during probing of reported on tumor ingrowth in two patients after 6 months, and N#{228}gele et al [28] used these stents in 10 patients and reported tumor ingrowth in three patients after a mean of 9 months.…”
Section: Twentymentioning
confidence: 99%
“…By employing self-expandable esophageal stents, we can expect the palliative relief of dysphagia resulting from stricture or obstruction of the esophagus (19,20). Presently, there exist the two following types of self-expandable stents: (a) covered and (b) uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, there exist the two following types of self-expandable stents: (a) covered and (b) uncovered. A covered metallic stent can be used effectively in patients who have developed malignant dysphagia associated with perforation or fistula formation (20,21). Although the covered type is preferred for the prevention of tumor overgrowth, which occurs in 5%-10% of patients (19), it is so much less flexible that it shows a greater tendency toward migration than the uncovered stent (20 -22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation